Primary Aspergillosis of Bilateral Laryngoceles - Zeyad Al-Ogaili; Gavin Chapeikin; David Palmer (Case Reports in Medicine)
Laryngocele is an abnormal dilatation of the saccule of laryngeal ventricle, which is usually unilateral and filled with air or fluid. We present a case of bilateral laryngoceles colonized by Aspergillus species.